2012
DOI: 10.1016/j.drugalcdep.2012.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis and depression: An integrative data analysis of four Australasian cohorts

Abstract: More frequent cannabis use was associated with modest increases in rates of depressive symptoms. This association was stronger in adolescence and declined thereafter. However, it was not possible from the available data to draw a definitive conclusion as to the likely direction of causality between cannabis use and depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
112
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(120 citation statements)
references
References 56 publications
(74 reference statements)
7
112
0
1
Order By: Relevance
“…According to the Diagnostic and Statistical Manual for Mental Disorders (DSM-IV), 1.6 million Americans used marijuana daily in 2000 and thus met the criteria for substance dependence (Wilson & Cadet 2009). Marijuana consumption is reported to increase the risk of mood or anxiety disorders, although the role of this drug as a cause of these disorders has yet to be established (Horwood et al 2012). With increasing demands to legalize marijuana, this possible link to mental disorders requires more research.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Diagnostic and Statistical Manual for Mental Disorders (DSM-IV), 1.6 million Americans used marijuana daily in 2000 and thus met the criteria for substance dependence (Wilson & Cadet 2009). Marijuana consumption is reported to increase the risk of mood or anxiety disorders, although the role of this drug as a cause of these disorders has yet to be established (Horwood et al 2012). With increasing demands to legalize marijuana, this possible link to mental disorders requires more research.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 20.1% of the patients diagnosed with bipolar disorder and 10.9% of patients diagnosed with depressive disorder also have comorbid substance use disorder (Nesvag, 2015). Horwood et al (2012) found an important linear connection between the frequency of marijuana use and the severity of depressive symptoms. Higher marijuana use is connected with a higher severity of depressive symptoms.…”
Section: Comorbidity Of Drug Usage and Psychiatric Disordersmentioning
confidence: 91%
“…Findings from the analysis of the integrated data improved knowledge of the relationships between cannabis use, mental health, other substance use and social development in young people (Horwood et al, 2010(Horwood et al, , 2012Silins et al, 2014). For example, the age of initiation of cannabis use was found to be a significant factor in educational attainment, with early use (i.e.…”
Section: What Has It Found? Key Findings and Publicationsmentioning
confidence: 98%
“…Selected PATH data on cannabis and depression have also been harmonised within this data set (Horwood et al, 2012). We intend to harmonise relevant data from all six cohorts in the CCRC subject to continued funding support.…”
Section: How Has the Ccrc Pooled Data Across Cohorts?mentioning
confidence: 99%